2014
DOI: 10.1016/j.orgel.2014.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonded diketopyrrolopyrrole (DPP) pigments as organic semiconductors

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 41 publications
0
92
0
4
Order By: Relevance
“…As in the case of other H-bonded pigment semiconductors, it is concluded that charge transport primarily occurs perpendicular to the H-bonding plane, along the two π-stacking directions. It cannot be excluded that, as was recently proposed for close H-bond interactions in diketopyrrolopyrrole compounds, [ 22 ] that a signifi cant probability of charge transport along the H-bonded chains also exists. The short H-bond lengths and close stacking interactions are together accountable for the high crystal lattice energy of epindolidione pigments, as observed by thermogravimetric (TGA) analysis ( Figure 3 ).…”
Section: Crystal Structurementioning
confidence: 92%
“…As in the case of other H-bonded pigment semiconductors, it is concluded that charge transport primarily occurs perpendicular to the H-bonding plane, along the two π-stacking directions. It cannot be excluded that, as was recently proposed for close H-bond interactions in diketopyrrolopyrrole compounds, [ 22 ] that a signifi cant probability of charge transport along the H-bonded chains also exists. The short H-bond lengths and close stacking interactions are together accountable for the high crystal lattice energy of epindolidione pigments, as observed by thermogravimetric (TGA) analysis ( Figure 3 ).…”
Section: Crystal Structurementioning
confidence: 92%
“…340,341 These pigments are synthesized from furfural and dialkylsuccinate ( Figure 26). Furfural is derived from biomass and is commercially available in large quantities at low cost.…”
Section: Low-cost Synthetic Semiconductorsmentioning
confidence: 99%
“…Recently, many small pigment molecules with fused hydrogen‐bonding have been reported to exhibit high charge carrier mobilities. Although those pigment molecules contain carbonyl and amine groups that have been regarded as perturbation groups for π‐conjugation; the strong intermolecular hydrogen‐bonding can serve as crystallization driving force to assemble those pigment molecules into highly ordered structure, which eventually leads to narrowed bandgaps and efficient charge transport between molecules.…”
Section: Introductionmentioning
confidence: 99%